Anthropometric and blood parameters for the prediction of NAFLD among overweight and obese adults - Kühn, Tilman; Stackelberg, Oyunbileg von; Schlett, Christopher L.; Kirsten, Romy; Kaaks, Rudolf; Kauczor, Hans-Ulrich; Nattenmüller, Johanna (BMC gastroenterology, 2018)
Non-alcoholic fatty liver disease (NAFLD) comprises non-progressive steatosis and non-alcoholic steatohepatitis (NASH), the latter of which may cause cirrhosis and hepatocellular carcinoma (HCC). As NAFLD detection is imperative for the prevention of its complications, we evaluated whether a combination of blood-based biomarkers and anthropometric parameters can be used to predict NAFLD among overweight and obese adults.
Gesehen am 24.07.2018